IS THERE ANYTHING LEFT OF ME?: SUBJECTIVITY AS A NEOLIBERAL COMMODITY (Quaestiones Disputatae: temas en debate, 2025)
Introduction: The reflection on the construction of subjectivity in the midst of the uncertainty, distrust and acceleration that characterize the present moment, constitute the backdrop of diverse intellectual approaches around the discomforts of the subject and the social whole. Objective: Therefore, it is necessary to ask oneself about the factors that configure subjectivity as neoliberal merchandise. Reflection: First of all, I would like to present, from an interdisciplinary perspective, the current context that has made possible the crisis of subjectivity in late capitalism. Then, to raise the articulation of this context with the emergence of a subject not only individualized, but also challenging a vision of life in the future. This through the elaboration of an argued proposal, derived from the reading of authors such as Deleuze, Foucault and Han. Conclusions: In the face of the changes that have characterized the last decade, the reflection accounts for a time frame loaded with business and technological nuances, to manage life. Even knowing that the consequences of such adoption have a specific face, reflecting the fragility of our human condition.
Keywords: Capitalism; Contemporary culture; Individualism; Daily life